Check sibling questions

Verify the following using Boolean Laws: A + C = A + A’. C + B.C

 

Answer:

To prove: A + C = A + A’. C + B.C 

 

Proof:

RHS

= A + A’. C + B.C 

= (A+A’).(A+C) + B.C                (using distributive law)

= 1.(A+C) + B.C                        (using complement law)

= A + C + (B.C)                         (using identity law)

= A + C.(1+B)                            (using distributive law)

= A + C.1                                   (using annulment law)

= A + C                                      (using identity law)

= LHS

Hence, the expression A + C = A + A’. C + B.C is verified.

Are ads bothering you?

Davneet Singh's photo - Co-founder, Teachoo

Made by

Davneet Singh

Davneet Singh has done his B.Tech from Indian Institute of Technology, Kanpur. He has been teaching from the past 12 years. He provides courses for Maths, Science, Social Science, Physics, Chemistry, Computer Science at Teachoo.